DINAMIKA INSTITUSI PERADILAN ISLAM DI INDONESIA - Rezal, Andi Rezal; Akmal, Andi Muhammad; Tenripadang, Andi (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2025)
The religious court institution in Indonesia plays a crucial role in implementing and upholding the application of law in the country. The research questions formulated in this study are: What is the religious court institution in Indonesia? And how has the dynamic of the religious court institution in Indonesia evolved? This study adopts a normative sharia approach with historical, legislative, and theoretical perspectives. The data sources are primarily documents and other relevant literature that support the research. The collected data is analyzed using content analysis. The results of this study indicate that the religious court institution in Indonesia is not a new phenomenon; it has existed since the era of kingdoms (pre-independence) and has continuously developed and evolved in line with the times, culminating in the enactment of regulations on Judicial Power, which form the legal basis for the religious court system in Indonesia. Furthermore, the dynamics of the religious courts in Indonesia involve various challenges related to contemporary social issues such as family resilience, gender equality, child and women's protection, and digitalization in response to modernization and globalization. The implications of this research are expected to serve as a foundation for historical reflection and highlight the need for further studies on current contemporary issues.